New R2-CHA2DS2-VASc score predicts no-reflow phenomenon and long-term prognosis in patients with ST-segment elevation myocardial infarction after primary percutaneous coronary intervention - Zhang, Qinyao; Hu, Meirong; Ma, Shumei; Niu, Tiesheng (Frontiers in Cardiovascular Medicine, 2022)
Abstract Aims: Evaluating the prognostic validity of new R2-CHA2DS2-VASc score for no-reflow phenomena and long-term prognosis in patients following primary percutaneous coronary intervention (PCI) with ST-elevation myocardial infarction (STEMI). Methods: From January 2017 to December 2018,a total of 401 patients with STEMI were continuously enrolled.According to the cut-off value,the patients were separated into two groups: R2-CHA2DS2-VASc<3 group (n=275) and R2-CHA2DS2-VASc ≥3 group (n=126). Results: With a sensitivity of 52.6% and a specificity of 73.1%,the optimal cut-off value for predicting no-reflow is R2-CHA2DS2-VASc ≥3. R2-CHA2DS2-VASc ≥3 as the ideal cut-off value for predicting major adverse cardiovascular events (MACE) with an area under the curve (AUC) of 0.781 (95% Confidence interval [CI]: 0.738-0.801, P 0.001), a sensitivity of 50%, and a specificity of 91.1%. The incidence of MACE, death from all causes,and worsening heart failure was greater in the R2-CHA2DS2-VASc ≥3 group, although there was no significant difference in the incidentce of repeated revascularisation procedures following PCI between the two groups.. R2-CHA2DS2-VASc ≥3 was also an independent predictor of MACE (hazard ratio = 2.48, 95% confidence interval CI: 1.33-4.62, P = 0.04). Moreover, this score has a greater sensitivity (66.7%) and specificity (88.7%) for predicting the progression of heart failure. Conclusion: R2-CHA2DS2-VASc ≥3 was independently associated with no-reflow phenomenon and poor clinical outcomes for patients in STEMI after primary PCI.